Ventricular tachycardia in normal heart - Raut, B; Malla, Sabita (Nepalese Heart Journal, 2000)
Ventricular tachycardia is usually thought occurring only in abnormal heart. But it can also occur in apparently normal heart. Cardiovascular evaluation is normal except for the arrhythmia. Monomorphic ventricular tachycardia is not always induced at electrophysiological study. The natural history isincompletely known, but recurrences are not uncommon. Antiarrhythmic drugs, radiofrequency catheter ablation and implantable defibrillators are useful therapeutic choices.Prognosis is good even though occasional cases of sudden deaths have been reported.